Schizosaccharomyces pombe and its Ni(II)-insensitive mutant GA1 in Ni(II) uptake from aqueous solutions: a biodynamic model - SAYAR, AHMET ALP; KAZAN, DİLEK; SAYAR, NİHAT ALPAGU; DURMAZ ŞAM, SELÇEN (SPRINGER, 2014)
In the present study, Ni(II) uptake from aqueous solution by living cells of the Schizosaccharomyces pombe haploid 972 with h (-) mating type and a Ni(II)-insensitive mutant GA1 derived from 972 was investigated at various initial glucose and Ni(II) concentrations. A biodynamic model was developed to predict the unsteady and steady-state phases of the uptake process. Gompertz growth and uptake process parameters were optimized to predict the maximum growth rate mu (m) and the process metric C (r), the remaining Ni(II) content in the aqueous solution. The simulated overall metal uptake values were found to be in acceptable agreement with experimental results. The model validation was done through regression statistics and uncertainty and sensitivity analyses. To gain insight into the phenomenon of Ni(II) uptake by wild-type and mutant S. pombe, probable active and passive metal transport mechanisms in yeast cells were discussed in view of the simulation results. The present work revealed the potential of mutant GA1 to remove Ni(II) cations from aqueous media. The results obtained provided new insights for understanding the combined effect of biosorption and bioaccumulation processes for metal removal and offered a possibility for the use of growing mutant S. pombe cell in bioremediation.
Keywords: Schizosaccharomyces pombe; Bioaccumulation; Bioremediation; Mathematical modeling; Nickel; HEAVY-METALS; NICKEL(II) IONS; NI II; BIOSORPTION; YEAST; BIOACCUMULATION; REMOVAL; BIOMASS; COPPER(II); CR(III)